Operator Suspicion and Decision Responses to Cyber-Attacks on Unmanned Ground Vehicle Systems. (September 2017) - Gay, Chris; Horowitz, Barry; Elshaw, John; Bobko, Philip; Kim, Inki
Cyber-attacks against cyber-physical systems (CPS), such as unmanned vehicles, are emergent threats with potentially catastrophic impacts, and this issue has drawn considerable interest by military agencies. Abundant body of research has attempted to address the physical security aspects of CPS; however, research addressing the human dimensions of cyber-attack detection and responses from an operator and operational perspective is sparse. This research has provided a novel probe into the human factors affecting operator resilience in responding to cyber-attacks, which are situations characterized by uncertainty and malicious intent. The variability of individual operators makes it improbable to grasp the full range of factors contributing to operator performance; however, the application of Suspicion Theory as proposed by Bobko et al. (2013), provides a starting point to aid in understanding operator performance in situations involving malicious intent (e.g. a cyber-attack). According to the theory, malicious intent is a critical component of operator suspicion, which is a key factor in operator response to cyber-attacks. The current research explored this human dimension through scenario-based, human-in-the-loop simulation experiments with Air Force personnel. It included both abstract and empirical assessments of the application of Suspicion Theory to operator detection and responses to cyber-attacks against an unmanned vehicle system, and it took a systems-oriented approach to the problem by considering the interaction of a Human-Machine Team (HMT) in the response. The HMT here refers to an operator and a Sentinel, which is an automated cyber-attack detection aid. The study evaluated the effects of suspicion, as well as the effects of perceived consequence, on the operator, and the resulting HMT quality of performance in responding to alerts, including both false alarms and properly detected cyber-attack scenarios. The findings show that Sentinel alerts alone do not create operator suspicion. Instead, alerts can serve as a catalyst for a wider information search by the operator, which, on a situational basis can lead to formation of increased operator suspicion. The analysis of experimental results pointed to a negative correlation between operator suspicion and performance score that measured the quality of a response to the given scenario. In addition, a strong correlation between HMT performance score and task response time was noted.